Age and maturity effects on morphological and physical performance measures of adolescent judo athletes - Giudicelli, B. B.; de Oliveira Luz, L. G.; Santos, D. H. B.; Sarmento, H.; Massart, A. G. M.; da Cunha Júnior, A. T.; Field, A.; Figueiredo, A. J. B. (Journal of Human Kinetics, 2021)
Studies assessing age and maturation effects on morphological and physical performance measures of young judokas are scarce. This study aimed to assess the independent and combined effects of chronological age and biological maturation on anthropometry and physical performance of 67 judokas aged 11-14. Participants` anthropometric profiles were assessed, and physical performance tests were completed. Multivariate analyses of variance revealed an independent effect of age (anthropometry: F = 1.871; p < 0.05; Pillai`s trace = 0.545; n2p = 0.272; physical performance: F = 2.876; p < 0.01; Pillai`s trace = 0.509; n2p = 0.254) and maturity (anthropometry: F = 10.085; p < 0.01; Pillai`s trace = 0.669; n2p = 0.669; physical performance: F = 11.700; p < 0.01; Pillai`s trace = 0.581; ç2p = 0.581). There was no significant combined effect of age and maturity. The maturation effect remained significant when controlled for age (anthropometry: F = 4.097; p < 0.01; Pillai`s trace = 0.481; n2p = 0.481; physical performance: F = 3.859; p < 0.01; Pillai`s trace = 0.0.318; n2p = 0.318). Inadolescent judokas, the maturation effect on growth and physical performance seems to be more relevant than the age effect, leading to the need to control this effect in training routines and competitive events. As in studies with youth soccer players and other youth athletes, bio-banding can be a strategy for controlling maturation in combat sports.